극한지 온도조건에 파이프라인 내부 열유동 영향변수 평가 - 조철희(Chul H Jo); 황수진(Su Jin Hwang); 장춘만(Choon Man Jang); 이준호(Jun Ho Lee) (한국수소 및 신에너지학회 논문집, 2014)
This paper describes thermal flow characteristics in various pipelines: straight pipeline and curved pipeline. In the permafrost area, pipelines are exposed to an extremely low temperature ($-40^{°}C$). In this situation, three-dimensional flow analysis should be analyzed to investigate thermal effects such as pressure drop, temperature change, velocity deficit and distribution change of liquid droplet of internal fluid. In this paper, multi-phase and multi-species analysis was introduced to analyze the flow characteristics of permafrost pipelines on the vertical support members above ground.